Bonding Effectiveness of Contemporary Materials in Luting Glass-Ceramic to Dentine: An In Vitro Study. Issue 1 (May 2021) - Mutlu, Alev; Atay, Ayse; Çal, Ebru
Aim: To evaluate the shear bond strength (SBS) of resin cements, flowable composites, and a preheated composite in luting glass-ceramic to dentin. Materials and Methods: In total, 108 noncaries human third molar teeth embedded in acrylic blocks, grinded from the occlusal surfaces until dentin was exposed, and divided into 9 randomized groups ( n = 12). In total, 108 ceramic samples prepared in disc shape (3mm × 3mm) from IPS e. max CAD (Ivoclar Vivadent) blocks. Four adhesive resin cements: Variolink Esthetic DC (Ivoclar Vivadent), G-CEM LinkForce (GC), Panavia V5 (Kuraray Noritake), Maxcem Elite Chroma (Kerr), and three flowable composites: G-ænial Universal Flo (GC), Herculite XRV Ultra Flow (Kerr), Vertise Flow (Kerr), and one preheated composite: Enamel Plus HRI (Micerium) luted to the prepared occlusal surfaces of the teeth with total-etch, self-etch, and self-adhesive protocols. Then samples were thermocyled (5, 000 cycles, 5–55°C, dwell time 20 s). SBS test was performed in a universal testing machine (at 0.5 mm/min). Failure modes were examined under a stereomicroscope at ×25 magnification. Data were analyzed using Kruskal–Wallis and Dunn–Bonferroni tests ( α = 0.05). Results: There were statistically significant differences among material types ( P < .05). Highest SBS values found in G-ænial Universal Flo (15.43 ± 5.67), and the lowest values obtained in Maxcem Elite Choroma (SA) (1.25 ± 1.47). There were no significant differences between self-etch (Panavia V5, Maxcem Elite Choroma [SE]) and self-adhesive (Maxcem Elite Choroma [SA], Vertise Flow) protocols ( P > .05). Conclusion: Flowable composites can be alternatives to resin cements when bonded with total-etch procedures. Bond strength of self-etch and self-adhesive applications is still to be developed.